No decrease in f ratio (ratio of Festuca‐specific genome region to the whole genome) in maternally derived progeny of festulolium (Festuca pratensis × Lolium species) across generations. (30th October 2015) - Kubota, Akito; Akiyama, Yukio; Fujimori, Masahiro; Kiyoshi, Takako
Abstract: Festulolium is an outbred, intergeneric hybrid between Lolium and Festuca species that might possess the agronomic advantages of both genera. As a result of DNA recombination, the chromosomes in festulolium are striped with DNA from the two genera. Using genomic in situ hybridization and image analysis techniques, we determined the genomic constitution of festulolium based on the ratio of Festuca ‐specific genome regions to the whole genome (the "f ratio"). Some researchers have observed a drift in the genome balance in favor of Lolium over successive generations in amphiploid festulolium plants resulting from the cross between Lolium species and Festuca pratensis . In order to uncover the cause of the drift in favor of Lolium, we checked the f ratio drift between maternal plants and their progenies in three populations. One of the populations was a single cross progeny between parents of the backcrossed cultivar 'Icarus, ' while the other two populations were isolated progenies of the amphiploid cultivar 'Nakei 1.' Because Lolium species produce more seeds than Festuca species, bulking of the seeds could cause the drift in favor of Lolium . In order to avoid this, progenies were maternally derived. In the present study, very few progeny plants had f ratios greater than 58%. The genomic drift in favor of Lolium in other studies might be due to the lack of very high f ratio plants. However, at least for one generation and with maternally derived progenies, Festuca chromosomal fragments did not disappear in either amphiploid or backcrossed festulolium cultivars, and the f ratio drift in favor of Lolium did not occur.